2006
DOI: 10.1188/06.onf.e90-e99
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Among Asian Americans: Is Acculturation Related to Health-Related Quality of Life?

Abstract: Closer attention is needed regarding acculturation level; Asian American subgroup differences, including language capacity; and socioecologic characteristics in nursing practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…There were differences in HRQOL within the groups with Koreans reporting worst outcomes. A fuller discussion relevant to Asian American HRQOL is beyond the scope of this paper, and will be presented in a separate paper [71]. Further, these results suggest possible ethnic variations in the predictors of HRQOL.…”
Section: Discussionmentioning
confidence: 92%
“…There were differences in HRQOL within the groups with Koreans reporting worst outcomes. A fuller discussion relevant to Asian American HRQOL is beyond the scope of this paper, and will be presented in a separate paper [71]. Further, these results suggest possible ethnic variations in the predictors of HRQOL.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, some research has demonstrated the importance of a significant other's support during physical and mental illness recovery (McClement et al 1997, Ganz et al 2002, Han 2003, Ashing-Giwa et al 2004. Social support, from both family and non-family, also seems to be an important situational resource that can attenuate depressive symptoms and, in turn, improve overall health and QOL for KICS (Kim et al 2006). Thus, understanding acculturation, social support, and depressive symptoms and their relationship to QOL would help illuminate the magnitude and type of mechanisms through which acculturation affects QOL for KICS.…”
Section: The Role Of Social Supportmentioning
confidence: 94%
“…Women with cancer may be more depressed, which makes it more difficult for them to cope with their illness than men with cancer (Segrin et al 2005). Risk factors such as being female, being a cancer survivor, and adjusting to a new society make KICS more susceptible to depressive symptoms (Baider et al 1996, Kim et al 2006. As depressive symptoms tend to increase physical effects and difficulties in managing cancer side effects, they may lower QOL (Badger et al 2004, Manne et al 2004.…”
Section: Introductionmentioning
confidence: 97%
“…For cancer survivors specifically, fear of recurrence and distress related to physical compromise are other psychological effects [36][37][38]. Additionally, several studies have documented that psychological well-being influenced PQOL through social support [39][40][41][42].…”
Section: The Contextual Model Of Hrqolmentioning
confidence: 99%